A BIBLIOMETRIC ANALYSIS OF TALENT MANAGEMENT:” CO-CITATION AND CLUSTER PERSPECTIVES” - Bhadoriya, Nishu; Dixit, Abhilasha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current study’s goals are to compile the body of knowledge on talent management, trace its historical evolution, examine the intellectual and social structures that underpin it, and suggest cluster-based issues for further talent management research. Donthu et al. (2021) suggested a framework-based bibliometric review that used the Scopus database to retrieve literature. Researchers used the VOS Viewer tool to analyse and present data in both tabular and graphical formats for descriptive and network analysis. The conceptual structure of the bibliographic data in this research area was made clear via co-citation analysis. Four-word frequency clusters were found by this research. Furthermore, it was demonstrated by author cooperation network analysis that in order to understand talent management, researchers looked into a variety of subjects, such as cultural influences, gamifications, social endorsements, and sustainability practices in the various contexts. By using network analysis to produce cluster-based themes, the study introduces a fresh methodology and provides insightful advice for future talent management research projects. Using the Scopus database is another novel feature that shows a deliberate attempt to thoroughly synthesize the literature and include a range of viewpoints and conclusions in the study.